2017
DOI: 10.1155/2017/4201809
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Exopolysaccharide Produced byStreptococcus thermophilusCC30

Abstract: An exopolysaccharide (EPS) producing strain CC30 was isolated from raw milk and identified as Streptococcus thermophilus with morphological and 16S sequencing analysis. The strain was shown to produce 1.95 g/L of EPS when grown in skim milk lactose medium at 30°C by increasing the viscosity of the medium. The EPS was isolated and purified, and it was shown to consist of glucose and galactose in 1 : 1 ratio, with molecular weights ranging from 58 to 180 kDa. FTIR spectroscopy indicated the EPS to have amide, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(46 citation statements)
references
References 37 publications
4
41
1
Order By: Relevance
“…Total antioxidant activity of EPS was determined using method of Mitsuda et al [ 41 ] as reported by Kanamarlapuda and Muddada [ 42 ]. Mixture of 1.235 g of ammonium molybtate (4 mM), 0.6 M Sulfuric acid (45 mL), 0.9942 g of Sodium sulphate (28 mM) and 250 mL with distilled water was used as total antioxidant capacity.…”
Section: Methodsmentioning
confidence: 99%
“…Total antioxidant activity of EPS was determined using method of Mitsuda et al [ 41 ] as reported by Kanamarlapuda and Muddada [ 42 ]. Mixture of 1.235 g of ammonium molybtate (4 mM), 0.6 M Sulfuric acid (45 mL), 0.9942 g of Sodium sulphate (28 mM) and 250 mL with distilled water was used as total antioxidant capacity.…”
Section: Methodsmentioning
confidence: 99%
“…In the establishment of Aβ 1-42 group, cells were induced by 10 μM of Aβ 1-42 for 24 h. In protective experiments of l-EPSs, cells were pretreated with various concentrations (100, 250, 500, 1000, and 1250 μg/mL) of l-EPSs dissolved in serum-free media for 24 h respectively, and then exposed to 10 μM (final concentration) of Aβ 1-42 in the presence of l-EPSs for another 24 h. The control cells were added with the same medium without Aβ 1-42 . All experiments were repeated three times for each treatment condition 19,20 .…”
Section: Metal Ion Chelating Activitymentioning
confidence: 99%
“…The freestanding Au and Ag films were put on a glass surface. The Si probes coated with Au had the sizes below: chip size, 3.6 * 1.6 * 0.4 mm, the radius of curvature, 10 nm; tip height 10-15 m. The Nova software was used to analyze the images 19,20 .…”
Section: Afm Imagingmentioning
confidence: 99%
“…Absence of peak around 1529.8 cm -1 which corresponds to an amino group was absent in our case. A peak at 1214 cm −1 corresponded to the presence of C-O stretching in ether or alcohol groups 24 . The peak around 1025 cm −1 recommended the presence of C-O-H link bond position 22 .…”
Section: Probiotic Propertiesmentioning
confidence: 99%